Ground reaction force as a factor responsible for the topography of injuries in professional dance. An analysis of three dance styles: classical dance, modern dance, and folk dance - Joanna Gorwa; Katarzyna Nowakowska-Lipiec; Robert Michnik (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: The study aimed to identify the effects of ground reaction forces (GRF) recorded during landing in typical elements of three dance styles, including classical, modern, and folk dance, on injuries` topography. METHODS: The research involved a survey and measurements of GRF generated during landing after the jump. The survey involved a group of 90 professional dancers. In the questionnaire, the dancers marked areas of the human body that were affected at least once by injuries. Biomechanical tests of the GRF recording were conducted on a group of 15 professional dancers. The analysis focused on the following parameters: a maximum value of the vertical variable of the GRF relative to body weight (maxGRF_z), the time between the moment from first foot contact with the ground to the moment of reaching the maxGRF_z (_tmaxGRFz), and the loading rate of the GRF relative to body weight (LR_GRFz). RESULTS: Regardless of dance style and sex, the lower spine, knee joints, ankle joints and feet were the areas most affected by injuries among professional dancers. The level of maxGRF_z, t_maxGRFz and LR_GRFz during typical jumps in classical, modern, and folk dance was statistically significantly different (P<0.01*). The highest mean maxGRFz values were recorded for jumps performed by classical dancers. Furthermore, the sum of injury-affected areas differed significantly across various dance styles and was connected with the impact forces transferred by the dancer's musculoskeletal system. CONCLUSION: The level of GRF is one of the decisive factors affecting the topography of professional dance injuries.